(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: The aim of the study was to evaluate the vital anatomical structures in the mandibular inter foramin region and to investigate the presence of sexual dimorphism with respect to the left and right sides region using CBCT. Materials & Method: A total of 60 CBCT scans (30 male & 30 female) were analysed for the MF position & shape, presence and measurement of AL & MIC (both in mm), patterns of emergence of mandibular canal, symmetry of MF & AL. All the scans were taken by CS 9300 (Care stream Health India Private Limited) CBCT machine adjusted at 80 kVp, 15mA, Voxel size 0.3x0.3x0.3 and field of view (FOV) of 10x5 (mandible only). The acquired images were reconstructed into multiplane views (axial, panoramic and cross-sectional) for evaluation. Results: Position 4 of MF (below the apex of second premolar) was most common on right side while position 3 (between first & second premolar) on left side, with 75% of symmetrical MF position. The prevalence of MIC was noted in 93.75% of the patients with mean length of 12.09±5.95 mm. The prevalence of AL was 53.13% with mean length of 1.07±1.42mm. Conclusion: The present study recommends a CBCT evaluation of inter-foraminal anatomical structures before planning the placement of implants. However, no sexual dimorphism was found regarding these parameters.